Improving Speaking Skills Using the Beyond Centers and Circle Time (BCCT) Technique - Anna Fauza Jailani; Zulfadli A. Aziz; Siti Sarah Fitriani (Universitas Syiah Kuala, 2018)
The objectives of this study were to find out: (1) If there would be a significant difference in speaking achievement between students who were taught-learnt speaking using the Beyond Centers and Circle Time (BCCT) technique and those who were taught-learnt speaking with the standard technique, and to find out (2) What would be the response of the students towards the use of the BCCT method. This experimental study was conducted with pre-school children at the TKIT Permata Sunnah in Banda Aceh in the 2017/2018 academic year. The sample for this research was two classes selected by random sampling: class B was the experimental class and class A was the control class. The data was collected with a speaking test plus interviews. An interview was used instead of a questionnaire, for answering the second research question, because the participants in this study were pre-school children. The data was analyzed using a t-test for the speaking test and collecting descriptions with an interview guide. The results showed that: (1) the BCCT technique was effective to increase the speaking skills of the pre-schoolers, which was proven by the result from the t-test, in which tcount (8.96) was higher than ttable (4.01); (2) the students generally had a positive response (80%) toward the use of the BCCT in their speaking classroom. Therefore, it can be concluded that the BCCT method was effective for improving the speaking skills of the pre-schoolers as well as providing many other advantages for them.